2022
DOI: 10.1002/cbf.3733
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects gingival mesenchymal stem cells and promotes differentiation into osteoblasts

Abstract: Melatonin (MEL) has antioxidant properties and participates in osteogenic differentiation. In periodontitis, in which increased oxidative stress and bone resorption are involved, mesenchymal stem cells derived from the gingiva (GMSCs) combined with MEL could be relevant for osteogenic regeneration. In this study, we studied the antioxidant and differentiating effect of MEL on an in vitro system of GMSCs. Primary culture of GMSCs from Wistar rats was developed to evaluate differentiation into osteoblasts with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Some studies have proven that melatonin promotes osteogenesis more efficiently in pathological cases than in osteoporotic defects [ 34 , 57 ] or periodontitis [ 58 ]. Data have shown that this process is related to the activation of the PI3K/AKT/mTOR pathway in stem cells after cell damage with, e.g., dexamethasone [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have proven that melatonin promotes osteogenesis more efficiently in pathological cases than in osteoporotic defects [ 34 , 57 ] or periodontitis [ 58 ]. Data have shown that this process is related to the activation of the PI3K/AKT/mTOR pathway in stem cells after cell damage with, e.g., dexamethasone [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is a human hormone with various functions in human health, such as keeping humans safe from certain cancers, delaying senescence, stimulating type I collagen fiber formation, and improving bone formation. Due to the increasing levels of free radicals during periodontal diseases, the level of antioxidants, such as melatonin, will be raised in the saliva to protect the oral cavity against oxidative stress and regenerate alveolar bone and collagen fibers [ 102 , 103 ]. In addition, melatonin increases collagen IIIα1, decorin, and IL10; It also decreases the matrix metalloproteinase 1 (MMP1)/tissue inhibitor metalloproteinase protein 1 (TIMP1) ratio, which is suitable for alveolar bone formation in the oral cavity.…”
Section: Role Of Antioxidant Materials In the Tissue Regeneration Pro...mentioning
confidence: 99%
“…In addition, melatonin increases collagen IIIα1, decorin, and IL10; It also decreases the matrix metalloproteinase 1 (MMP1)/tissue inhibitor metalloproteinase protein 1 (TIMP1) ratio, which is suitable for alveolar bone formation in the oral cavity. Regarding this, Sola et al [ 103 ] analyzed the antioxidant and osteogenic differentiation effects of melatonin on mesenchymal stem cells derived from the gingival mesenchymal stem cells (GMSCs). Results showed that melatonin protected GMSCs in a model of cellular damage (resulting from oxidative stress).…”
Section: Role Of Antioxidant Materials In the Tissue Regeneration Pro...mentioning
confidence: 99%